Categorizing threatened species: an analysis of the Red List of the flora of Brazil. Issue 2 (April 2014) - Moraes, M. A.; Borges, R.A.X.; Martins, E. M.; Fernandes, R. A.; Messina, T.; Martinelli, G.
Abstract In Brazil most of the effort for the conservation of plant species has comprised evaluation of taxa for the Lista Oficial das Espécies Ameaçadas de Extinção da Flora Brasileira (Official Threatened Flora Species List), and little has been done to conserve individual species. This is a result of the listing process being interpreted as the final goal rather than as a means to achieve conservation effectiveness. In addition, a variety of systems for the classification of extinction risk have been applied, resulting in an inaccurate view of the conservation status of the flora of the country. Here we review the national listing process to highlight the strengths and weaknesses of the Official Threatened Flora Species List. We used all available information to compile a list of taxa officially recorded as threatened in Brazil. The list was revised using the Flora do Brasil database. The resulting list has 4, 967 taxa in 1, 235 genera and 232 families. Despite controversies about advances in the Red Listing process, several improvements have been made at the institutional level, such as: (1) improving conservation databases, (2) developing information systems, and (3) increasing the number of taxonomists working in conservation biology. However, there is still no classification system for extinction risk that facilitates standardization of the listing process at the national level. In addition, regulatory processes related to the conservation of threatened plant species are not up-to-date with the conceptual and methodological advances made by the scientific community. We conclude that adjustments are needed to ensure the effectiveness of the conservation of plant species in Brazil.